Pembentukan Karakter Religius Siswa berbasis Pembiasaan dalam Kegiatan Ekstrakurikuler di Madrasah - Muhammad Hasyim; Afifatun Najibah (Journal of Education and Religious Studies, 2022)
This study discusses the formation of habituation-based students' religious character in extracurricular activities at MTs. Roudlotul Qur'an Lamongan. In forming the religious character of students, all these activities must be designed as well as possible so that all students have good morals, not only at school but wherever they are. This type of research is a descriptive qualitative research with a case study approach and data analysis of Miles, Huberman, and Saldana. The results of the research show that the religious character values applied in MTs. The integrated Roudlotul Qur'an Lamongan is obedience to Allah SWT, gratitude, honesty, fairness, sincerity, patience, independence, courtesy, discipline, respect, responsibility, caring, confidence, creative and active. As for the formation of religious values through scheduled activities outside of learning hours, namely extracurricular activities including Qiro'ah, Banjari, Scouts, PALA (Nature Lovers), and Calligraphy. While habituation activities include congregational dhuha prayers, tartil, learning the Qur'an for non-mukim students, congregational dhuhur prayers, Istighosah, Rotibul Haddad on Friday morning and completing the Qur'an on Friday at the first month, and the commemoration of Islamic Holidays. And habituation activities that are general in nature such as flag ceremonies/morning apples, sports and maintaining school cleanliness, as well as moral habit or student behavior such as shaking hands in the morning.